2010
DOI: 10.4314/swj.v3i4.51823
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of <i>Clarias gariepinus</i> and <i>Tilapia zilli</i> at Lamingo dam, Jos, Nigeria.

Abstract: Under natural conditions, 50-90% of fresh water fishes harbor at least one species of parasites (Sieszko, 1975;Daniel, 1978). Parasitism is much more common and diversified in the wild than in the farms, ponds and hatcheries. Infections occur not only due to over crowding but also due to environmental stress. As a result, fish exposed to virulent pathogens under environmental stress such as temperature, sewage, metabolic waste products of fishes, pollution and pesticides 23 ABSTRACTThe study was undertaken to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
18
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 3 publications
9
18
3
Order By: Relevance
“…The absence of acanthocephalan in this research could probably be due to the fact that it was carried out during the rainy season. The earlier work of Goselle et al (2008) and few others showed that helminths have preference for region of attachment in the alimentary canal of fish. In this study, the distribution of gastrointestinal helminth parasites in the fishes showed a clear preference for the intestine and stomach as sites of attachment which could be attributed to the availability of food in these regions.…”
Section: Discussionmentioning
confidence: 95%
“…The absence of acanthocephalan in this research could probably be due to the fact that it was carried out during the rainy season. The earlier work of Goselle et al (2008) and few others showed that helminths have preference for region of attachment in the alimentary canal of fish. In this study, the distribution of gastrointestinal helminth parasites in the fishes showed a clear preference for the intestine and stomach as sites of attachment which could be attributed to the availability of food in these regions.…”
Section: Discussionmentioning
confidence: 95%
“…Respondents level of awareness with the reports of Goselle et al (2008) who reported a prevalence of 36.9% at an agro-ecologically equivalent Lamingo Dam in western Nigeria. However, it was by far lower than previous reports of 75.67% by Zelalem Temesgen (2003) at Lake Hawassa, and 43.4% by Bichi and Ibrahim (2010) in Tilapia species in Tiga Lake, Northern Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding habit of this class of fish exposes them to sources of infection by fish parasites (Biu and Nkechi, 2013). Previous researches have reported that 50 to 90% of Tilapia species harbor at least one species of gastrointestinal parasites (Goselle et al, 2008). Parasitism is much more common and diversified in the wild compared to the farms, ponds and hatcheries.…”
Section: Introductionmentioning
confidence: 99%
“…Infections occur not only due to overcrowding but also due to environmental stress. A research finding has shown that parasitic infections of Tilapia tend to decrease the growth rate (Goselle et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation